Starter Culture Modulates Microbial Diversity During Wine-Coffee Fermentation: A DGGE-Based Molecular Study - Nasir, Fitri Handayani; Astuti, Dea Indriani; Taufik, Intan; Fitriagustiani; Ikramullah, Muh. Chaeril; Putri, Nurul Febriani; Pasmawati (Al-Hayat: Journal of Biology and Applied Biology, 2025)
Wine-flavored coffee is a unique post-harvest product characterized by fruity, acidic, and winey notes, highly favored by Indonesian consumers and possessing strong potential in the global market. However, maintaining consistency in flavor and quality remains a challenge due to the variability of natural fermentation. This study aimed to evaluate the impact of yeast and bacterial starter culture inoculation on microbial community dynamics during wine-coffee fermentation, using a molecular approach based on PCR-DGGE. DGGE analysis revealed that natural fermentation without inoculation involved diverse populations of bacteria, yeasts, and filamentous fungi, with eukaryotic microbes dominating from the early stages. Sequencing identified prevalent yeast genera including Pichia, Torulaspora, Hanseniaspora, Saccharomyces, and Candida, as well as Aspergillus among filamentous fungi. Bacterial communities were dominated by lactic acid bacteria and members of Lactobacillus, Klebsiella, Enterobacter, Pantoea, and Bacillus. In contrast, controlled fermentation with inoculated starter cultures (Pichia kudriavsevii and Klebsiella sp.) showed a more stable microbial profile throughout the process. Shannon-Wiener diversity indices demonstrated a significant difference (p = 0.05) between natural and inoculated fermentations, with species dominance observed in the latter. Cluster analysis confirmed that starter culture inoculation significantly influenced microbial succession and community structure. These findings highlight the importance of controlled fermentation using selected microbial starters to ensure consistent microbial ecology, which in turn contributes to reproducible quality in wine-flavored coffee. The molecular profiling approach provides valuable insights for improving fermentation practices and developing reliable starter culture formulations tailored to enhance flavor consistency and product quality.